2022
DOI: 10.1155/2022/7971169
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Immune Checkpoint Inhibitor-Induced Aortitis Treated with Tocilizumab

Abstract: Vasculitic immune checkpoint inhibitor-related adverse events (irAEs) are rare, with limited data to guide their management. Here, we present a case of a 67-year-old female with stage IV cutaneous melanoma who received first-line pembrolizumab. She had completed 21 cycles of pembrolizumab dosed at 200 mg every 21 days over 15 months when she developed fatigue, chills, decreased appetite, night sweats, nausea, diarrhea, dry cough, and chest pain. A routine, staging positron emission tomography (PET) scan reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Sato et al 11 reported a case of G‐CSF‐induced LVV with elevated serum IL‐6 levels, suggesting that IL‐6 is involved in the development of LVV. In contrast, ICIs have been shown to cause LVV as an immune‐related adverse event (irAE) 12,13 . ICI administration increases activated T‐cell infiltration into the vasculature and the levels of inflammatory cytokines, such as IL‐6, IL‐17, and interferon gamma, which may cause LVV 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Sato et al 11 reported a case of G‐CSF‐induced LVV with elevated serum IL‐6 levels, suggesting that IL‐6 is involved in the development of LVV. In contrast, ICIs have been shown to cause LVV as an immune‐related adverse event (irAE) 12,13 . ICI administration increases activated T‐cell infiltration into the vasculature and the levels of inflammatory cytokines, such as IL‐6, IL‐17, and interferon gamma, which may cause LVV 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The patient was subsequently switched to pembrolizumab without further aortic involvement. However, pembrolizumab has recently been linked to a case of transverse aortic arch aortitis [ 12 ] . Similar to the case presented here, the patient was undergoing treatment for metastatic melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…High-dose steroids was started and pembrolizumab was discontinued. However, high-dose prednisolone cause bothersome weight gain and insomnia leading to a change from prednisolone to tocilizumab as a steroid-sparing agent [ 12 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Vasculitis is classified into large-, medium-, and small-vessel types depending on blood vessel size [ 116 ], but ICIs can cause any type of vasculitis. In fact, giant cell arteritis (GCA) [ 117 , 118 ], aortitis and large-vessel involvement [ 119 , 120 , 121 ], IgA vasculitis [ 122 , 123 ], granulomatosis with polyangiitis [ 124 , 125 ], eosinophilic granulomatosis with polyangiitis [ 126 ], and cutaneous small-vessel vasculitis [ 127 , 128 ] have been reported after ICI administration. A retrospective pharmacovigilance study evaluated the association between ICIs and cardiovascular adverse events and demonstrated that ICI treatment was associated with a higher risk of vasculitis when compared with the database obtained from individual case safety reports [ 129 ].…”
Section: Rheumatic Iraesmentioning
confidence: 99%
“…Vasculitis caused by ICIs usually requires high-dose glucocorticoid treatment [ 77 ]. Other therapeutic options include cyclophosphamide [ 138 ], tocilizumab [ 119 ], rituximab [ 139 , 140 ], plasmapheresis [ 141 ], and JAK inhibitors [ 142 , 143 ]; however, the optimal management of ICI-induced vasculitis has not been established.…”
Section: Rheumatic Iraesmentioning
confidence: 99%